Analisis Laporan Keuangan Untuk Menilai Kinerja Keuangan Pada PT Astra International Tbk Periode 2014-2023 - Rina A; Hermawan, Hengki (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the financial statements of PT Astra International Tbk for the period 2014–2023 to assess the company’s financial performance. The method used is descriptive quantitative analysis, focusing on profitability and liquidity ratios, namely Return on Assets (ROA), Return on Equity (ROE), Current Ratio (CR), and Quick Ratio (QR). The data analyzed consists of annual financial reports obtained from the company’s official sources. The results show that the company’s profitability ratios fluctuated but remained at a fairly good level. Meanwhile, the liquidity ratios were below the industry standard, indicating challenges in the company’s ability to meet short-term obligations. This research is expected to provide a comprehensive overview of the company’s financial condition and serve as a basis for evaluating and improving future financial performance.